Reversible formation of networked porous Sb nanoparticles during cycling: Sb nanoparticles encapsulated in a nitrogen-doped carbon matrix with nanorod structures for high-performance Li-ion batteries. Issue 42 (2nd October 2019) - Feng, Ping; Cui, Zhe; He, Shu-Ang; Liu, Qian; Zhu, Jinqi; Xu, Chaoting; Zou, Rujia; Hu, Junqing
Abstract : Due to networked porous formation of Sb nanoparticles after delithiation, the Sb@N-CM nanorods anode exhibits a high reversible capacity, high coulombic efficiency, and excellent rate capability. Abstract : Novel nanorods assembled from Sb nanoparticles encapsulated in a N-doped carbon matrix coated with a thin carbon layer (Sb@N-CM nanorods) were synthesized using a cation exchange reaction combined with a novel confined route. In situ transmission electron microscopy (TEM) observations verified that after delithiation, the Sb nanoparticles formed networked porous structures to enhance the utilization of active materials and close the connection between the Sb nanoparticles and N-doped carbon matrix for the first time; this can greatly improve the ion/electron transfer kinetics of a material. In addition, the Sb@N-CM nanorods not only improved the structural stability, stabilized the SEI layer and increased the transport of Li +, but also suppressed the SEI layer formation on the surface of individual Sb nanoparticles due to their advanced structural merits, such as coating with an N-doped conductive carbon layer and forming void spaces by a conductive carbon matrix, which can greatly increase the electrochemical performance. As a result, the Sb@N-CM nanorods exhibit a high reversible capacity (673.4 mA h g −1 at 100 mA g −1 ), ultrahigh cycling stability (99.7% capacity retention over 500 cycles), and excellent rate capability, which to our knowledge are the best cycling stability and capacity reported to date among all reported Sb-based materials.